2018
DOI: 10.7150/ijbs.23845
|View full text |Cite
|
Sign up to set email alerts
|

WDR1 Promotes Cell Growth and Migration and Contributes to Malignant Phenotypes of Non-small Cell Lung Cancer through ADF/cofilin-mediated Actin Dynamics

Abstract: The characteristic of carcinoma is cell migration and invasion, which involve in strong actin dynamics. Regulations of actin dynamics have been implicated in cancer cell migration and tumor progression. WDR1 (WD-repeat domain 1) is a major cofactor of the actin depolymerizing factor (ADF)/cofilin, strongly accelerating ADF/cofilin-mediated actin disassembly. The role of WDR1 in non-small cell lung cancer (NSCLC) progression has been unknown. Here, we show that the expression levels of WDR1 are increased in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…To determine whether tumors with different genotypes show distinct patterns of expression, we carried out a principle component analysis and hierarchical clustering and found that 3 independent tumors with WT expression of Fbxo9 clustered together while heterozygous and homozygous cKO tumors clustered together, indicating they are more similar to each other than to Cbfb +/56M Fbxo9 +/+ tumors (Figure 6E-F). Interestingly, a number of the top up-regulated proteins identified (PFKP, ADK, ARF1, TOMM34, DIAPH1, and WDR1) have been shown to participate in cancer by increasing cell growth and metastasis or are biomarkers for poor outcome (Figure 6F) 3439 .…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether tumors with different genotypes show distinct patterns of expression, we carried out a principle component analysis and hierarchical clustering and found that 3 independent tumors with WT expression of Fbxo9 clustered together while heterozygous and homozygous cKO tumors clustered together, indicating they are more similar to each other than to Cbfb +/56M Fbxo9 +/+ tumors (Figure 6E-F). Interestingly, a number of the top up-regulated proteins identified (PFKP, ADK, ARF1, TOMM34, DIAPH1, and WDR1) have been shown to participate in cancer by increasing cell growth and metastasis or are biomarkers for poor outcome (Figure 6F) 3439 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the 12 functional genes have been connected with COAD or other diseases according to the existing research. For example, TPM2 was reported to be in implicated in CRC [ 60 ]; STMN2 might be involved in beta-catenin/TCF-mediated carcinogenesis in human hepatoma cells [ 61 ]; CHMP4C was identified as a novel molecular target gene for ovarian cancer [ 62 ]; GRIA3 may act as a mediator of tumor progression in pancreatic cancer [ 63 ]; WDR1 was reported as a therapeutic target in lung cancer [ 64 ]; CPT2 was identified as a potential diagnostic biomarker of colon cancer [ 65 ]; Somatic deletion of KDM1A plays role in advanced colorectal cancer stages [ 66 ]; NFE2L1 , also called Nrf1, was found to be associated to high-risk diffuse large B cell lymphoma [ 67 ]; Gatza et al reported that TGFBR3 promotes colon cancer progression [ 68 ]; FGFR2 was shown to promote gastric cancer progression [ 69 ]. Therefore, the 12 functional genes probably play important roles in COAD and could be the potential prognosis biomarkers for COAD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as con rmed by luciferase reporter assay, our data also suggested that methylationmediated silencing of miR-1250-5p could result in upregulation of another direct target, WDR1. WDR1 was found to be upregulated and associated with poor prognosis in breast and lung cancer [41][42][43]. In lung cancer cells, the oncogenic function of WDR1 in the regulation of cellular proliferation was shown to be mediated by dephosphorylation and hence increased nuclear translocation of YAP protein, a downstream effector for Hippo signaling pathway, hence activation of the transcription of proproliferative genes, such as cyclin A2, cyclin B1, cyclin D1, cyclin E and Cdk1 [41].…”
Section: Discussionmentioning
confidence: 99%
“…WDR1 was found to be upregulated and associated with poor prognosis in breast and lung cancer [41][42][43]. In lung cancer cells, the oncogenic function of WDR1 in the regulation of cellular proliferation was shown to be mediated by dephosphorylation and hence increased nuclear translocation of YAP protein, a downstream effector for Hippo signaling pathway, hence activation of the transcription of proproliferative genes, such as cyclin A2, cyclin B1, cyclin D1, cyclin E and Cdk1 [41]. Moreover, in breast cancer cells, knockdown of WDR1 resulted in inhibition of cancer cell migration and invasion [42,43].…”
Section: Discussionmentioning
confidence: 99%